Chronic Granulomatous Disease Presenting as Aseptic Ascites in a 2-Year-Old Child - J. F. Moreau; John A. Ozolek; P. Ling Lin; Todd D. Green; Elaine A. Cassidy; Veena L. Venkat; Andrew R. Buchert (Case Reports in Immunology)
Chronic granulomatous disease (CGD) is a rare inherited immunodeficiency syndrome that results from abnormal nicotinamide adenine dinucleotide phosphate (NADPH) oxidase function. This defect leads to recurrent catalase-positive bacterial and fungal infections as well as associated granuloma formation. We review the case of a 2-year-old boy who presented with ascites and fever of an unknown origin as manifestations of CGD. Cultures were negative for infection throughout his course, and CGD was suspected after identification of granulomas on peritoneal biopsy. Genetic testing revealed a novel mutation in the CYBB gene underlying his condition. This paper highlights the importance of considering CGD in the differential diagnosis of fever of unknown origin and ascites in children.